Mathlete: an adaptive assistive technology tool for children with dyscalculia. - Dhingra, Kriti; Aggarwal, Rekha; Garg, Anchal; Pujari, Jayanti; Yadav, Divakar (Disability & Rehabilitation: Assistive Technology, 2024)
The use of technology in teaching and learning process for children is gaining importance. Children with specific learning disabilities have shown positive results with assistive technology tools. Dyscalculia is a specific learning disability in which an individual faces problem in mathematical skills. Around 3–7% of the world population is affected with it. The aim of the current research study is to determine the effectiveness of an assistive technology tool, Mathlete on children with dyscalculia's early numeracy skills. Such assistive technology tools can serve as a boon for these children. A total of 40 children with dyscalculia (Mage = 6.8 years) were a part of the study. The group of 40 children were randomly divided into two groups: experiment group using mathlete for improving their learning (30 children) and a control group using only traditional teaching for learning (10 children). The children were screened for dyscalculia using the screening module of mathlete. The two groups showed no significant difference in terms of their socio-economic status, gender and parents education level. Children in the experiment group showed improvement from pre-test to post-test after using mathlete. Also, there was significant difference in learning of both the groups, children in experiment group could understand the concepts better than the ones in control group. Mathlete helped improve the mathematical learning of children with dyscalculia from pre-test to post-test. Despite a huge prevalence of dyscalculia globally, this specific learning disability has always been overlooked due to lack of awareness and evident research. Assistive technology in form of computer aided instructions are the need of hour as children with special needs are usually neglected by many EdTech platforms, dyscalculia being a prominent one. An adaptive tool can give the child a customised experience thus developing interest in using the tool. Mathlete, focuses on early numeracy skills among children and helps them work on their deficit areas in their initial stages.